Bramante's Tempietto, the Roman Renaissance, and the Spanish crown - Freiberg, Jack (Cambridge University Press, 2014)
"The Tempietto, the embodiment of the Renaissance mastery of classical architecture and its Christian reinvention, was also the preeminent commission of the Catholic kings, Ferdinand of Aragon and Isabel of Castile, in papal Rome. This groundbreaking book situates Bramante's time-honored memorial dedicated to Saint Peter and the origins of the Roman Catholic Church at the center of a coordinated program of the arts exalting Spain's leadership in the quest for Christian hegemony. The innovations in form and iconography that made the Tempietto an authoritative model for Western architecture were fortified in legacy monuments created by the popes in Rome and the kings in Spain from the later Renaissance to the present day. New photographs expressly taken for this study capture comprehensive views and focused details of this exemplar of Renaissance art and statecraft"--